, DMCN 43: 234–8 (Developmental Medicine and Child Neurology, 2001)
Aim To systematically review the effectiveness, safety, and economic evidence of pharmacological and non-pharmacological interventions for sleep disorders in children with cerebral palsy (CP). Method Databases including MEDLINE, Embase, CENTRAL (the Cochrane Library), International Clinical Trials Registry Platform of the World Health Organization, NHS Economic Evaluation Database, and ClinicalTrials.gov were searched up to May 2026. Randomized controlled trials and economic evaluations were eligible. Primary outcomes included sleep quality, adverse events, and tolerability. We incorporated interest holder perspectives, including clinicians and individuals with lived experience, throughout outcome prioritization and interpretation. We assessed risk of bias using the Cochrane Risk of Bias 2.0 tool and evaluated the certainty of evidence using Grades of Recommendation, Assessment, Development and Evaluation. Results Twelve randomized controlled trials (n = 19-142, aged 5-17 years) were included. Pharmacological (melatonin, cannabis-based medicines, baclofen, neural stem cells) and non-pharmacological interventions (massage, cranial osteopathy, music therapy, acupuncture, postural support) were evaluated. Melatonin improved sleep latency and duration modestly compared with placebo. Other interventions showed inconsistent or negligible effects. Adverse events were mild and tolerability acceptable. No completed economic evaluations were identified. Interest holders highlighted the multifactorial nature of sleep problems, the need for interventions addressing comorbidities, and improved reporting of equity factors. Interpretation Evidence for managing sleep disorders in children with CP is limited, heterogeneous, and of low certainty. Robust trials and economic evaluations are urgently needed.